Measuring The Competitiveness of Footwear in The Global Market: A Comparison Study of Indonesia and Cambodia - Nurkomariyah, Siti; Sutjiatmo, Bayu Prabowo (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aims to compare the competitiveness of Indonesian and Cambodian footwear in the global market. Indonesia’s export value increased over the year, but in 2019 it significantly decreased. The footwear industry has grown negatively since 2019, and during the pandemic, the growth rate is -8.76%. In contrast, since 2019, Cambodia has become the 10th world's footwear exporter. It is undoubtedly a threat to Indonesia, so it is necessary to make various strategies to increase Indonesia's competitiveness. Revealed Comparative Advantage (RCA) and Export Dynamic Product (EPD) methods measure the competitive position. This study uses secondary data in the form of annual export from 2011 to 2020. The results show that Indonesia has a comparative advantage over the world but is moderate, with an RCA value of 3.81. Cambodia has more competitively than Indonesia, with an RCA index of 8.22. Even though in 2020 it experienced negative growth, Indonesia's footwear both comparatively and competitively increased. The RCA index value increases and the EPD is in the best position, "the rising star". Indonesian products have high market attractiveness and market share in the global.